Tourism Promotion in Tak Province using Virtual Reality Technology - Joobanjong, Wanchana; Sanchana, Wiraiwan; Mulom, Rung; Suesatsakulchai, Apichai (JOURNAL OF INFORMATION SCIENCE AND TECHNOLOGY, 2021)
The purpose of this study is to develop digital media, that has been applied the virtual reality technology, for tourism promotion in Tak province. This technology is an attractive tool to create simulated three-dimensional images or environments. It can build the tourists’ feel that they are similar in real places. The information was collected from the relevant expert. The digital media were developed using the unity application and virtual reality tools that help tourists to know the shape, proportion, and virtual display. These digital media and information about the attraction were presented together on web applications. The results of this evaluation showed that the users were satisfied with the digital media and web application at the highly level of satisfaction (x ̅ = 4.43, S.D. = .550).